Cost of Equity Capital and Accounting-based Drivers of Risk - Ali Saghafi; Ali Rahmani; Majid Motamedi Fazel (مجله دانش حسابداری, 2012)
According to the Capital Asset Pricing Model (CAPM), the only risk factor that investors should take into account in making their decisions is the systematic risk (β). Several studies have shown that the market risk (β) is not the only risk factor affecting the expected rate of return and there are other risk factors different to β. This paper analyzes the relevance of accounting fundamentals to inform about equity risk as measured by the cost of equity capital. Considering the cost of equity capital is a summary measure of how investors make decisions regarding the allocation of resources, the strength of the association between the cost of equity and accounting-based measures of risk, indicates how important these measures are for market participants when making economic decisions.  In this study, for estimating the cost of equity, three models O'Hanlon and Steel, Gordon and Capital asset pricing are used. Also, to test assumptions, regression method has been employed. The sample refers to 66 firms accepted in Tehran Stock Exchange along the period 1997–2008. Research results support the association between the cost of equity capital and some accounting-based risk variables, thereby supporting the usefulness of fundamental analysis to determine the risk.